(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article provides information on the intellectual development of primary school children based on the author’s methodology of teaching chess. In addition, it substantiates that “reprocessing practice” in chess is highly beneficial in many aspects: it not only improves game techniques but also serves as an important tool for developing players’ thinking, critical analysis, and self-assessment skills.